DOI: 10.1039/9781782620600-00149
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic receptors for molecular recognition of carbohydrates

Abstract: Section 1. Modification of the receptor binding side-arms. 15 Design and Synthesis…………………………………………………………... 15 Binding studies and structure elucidation…………………………………….. 18 Section 2. Modification of the receptor scaffold. 27 Design and Synthesis…………………………………………………………... 27 Binding studies and structure elucidation…………………………………….. 30 Section 3. Modifications of the pyrrolic binding groups. 37 Design and Synthesis…………………………………………………………... 37 Binding studies and structure elucidation…………………………………….. 39 Section 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The use of boronic acids, which form reversible covalent bonds with 1,2-or 1,3-diols, represents one strategy to bind carbohydrates in water (Jin et al, 2010;Zhai et al, 2015). Tripod-and cage-shaped molecules can act as lectin mimics, which accommodate carbohydrates through non-covalent interactions (Davis, 2009;Gentili et al, 2016;Mazik, 2012;Park et al, 2015). Although promising, these molecules tend to suffer from a lack of potency in water, a low selectivity among carbohydrates, or both.…”
Section: Introductionmentioning
confidence: 99%
“…The use of boronic acids, which form reversible covalent bonds with 1,2-or 1,3-diols, represents one strategy to bind carbohydrates in water (Jin et al, 2010;Zhai et al, 2015). Tripod-and cage-shaped molecules can act as lectin mimics, which accommodate carbohydrates through non-covalent interactions (Davis, 2009;Gentili et al, 2016;Mazik, 2012;Park et al, 2015). Although promising, these molecules tend to suffer from a lack of potency in water, a low selectivity among carbohydrates, or both.…”
Section: Introductionmentioning
confidence: 99%
“…For receptors falling out of these two types, please see the noted reviews. [31,[36][37][38] Under the category of covalent receptors, temple-shaped receptors and flexible receptors differ on the basis of their use of preorganization and structural rigidity. Inspired by the structural characteristics of D-glucose and single crystal structures of lectins, temple-shaped receptors (Figure 3) were designed to recognize all-equatorial D-glucose or D-glucosides.…”
Section: Synthetic and Biomimetic Saccharide Recognitionmentioning
confidence: 99%
“…[80] Roelens and co-workers have used persubstituted benzene (PSB) rings to construct various tripodal carbohydrate receptors, with efforts specifically for binding β-mannose, and showed that the aminopyrrolic tripodal receptors exhibited remarkable biological activity including antiviral function. [38,55] Due to the steric gearing, the PSB scaffold exhibits facial segregation of the respective substituents around the phenyl plane. [81] This unique stereochemical characteristic led to the development of tripodal receptors that bind certain carbohydrates without all-equatorial hydroxyl groups through the combination of hydrogen bond donors/acceptors as well as potential CH-π interactions for saccharide-aromatic stacking.…”
Section: Tripodal Receptorsmentioning
confidence: 99%
“…This strategy is extremely valuable for elucidation of the requirements for molecular recognition of carbohydrates and facilitates structure optimisation to achieve the appropriate geometry and functional group disposition for establishing effective binding interactions. A pragmatic user's guide in the nontrivial task of designing effective biomimetic CBAs was recently published by our group; nevertheless, some basic and general concepts in molecular recognition of carbohydrates are summarised here.…”
Section: Biomimetic Cbas: Design and Affinitiesmentioning
confidence: 99%